ANALYSIS OF THE NEEDS OF TEACHING PROGRAM STUDENTS FOR FLIPBOOK-BASED DESCRIPTION TEXT WRITING TEACHING MATERIALS - Oktarina, Santi (Logat: Jurnal Bahasa Indonesia dan Pembelajaran, 2024)
The development of the world of education is faced with challenges that demand innovation in the learning process. One of the reforms carried out is the development of technology-based teaching materials. The aim of this research is to describe an analysis of the needs of Teacher Professional Program students regarding the development of Flipbook-based descriptive text writing teaching materials. This research is part of research and development, namely in the research data collection stage. The method used is a survey. The object of this research is students of the elementary school teacher professional program. Data collection techniques in this research are questionnaires and interviews. The data analysis techniques used are quantitative data analysis techniques and qualitative analysis techniques. The research results show that students of the professional teacher study program, especially elementary school teachers, really need flipbook-based teaching materials in learning to write descriptive texts. This is viewed in terms of material, language and presentation of learning media